A sociocultural perspective on second language writing teacher cognition: A Vietnamese teacher's narrative. (November 2018) - Ngo, Xuan Minh
Abstract: Despite increased attention to social and historical dimensions in language teacher cognition research, the second language writing teacher cognition literature remains dominated by the cognitivist tradition that separates teachers' beliefs from their practices. To address this mismatch, this paper proposes to view second language writing teacher cognition through the lens of Vygotsky's sociocultural theory, particularly its genetic method and concept of mediation. Based on these frameworks, the study aims to reveal the major shifts in a Vietnamese English language teacher's cognition about second language writing and the mediating resources involved. Following the narrative design, the participant's professional life story was first constructed with data from a series of interviews and various national and institutional documents. Her narrative was then subject to thematic analysis guided by the sociocultural theory concepts. It was found that her cognition changes followed a complex, non-linear trajectory, and there were dialectical interrelationships between these shifts. Moreover, these shifts were mediated by humans, concepts, and artifacts, whose influence was simultaneous and dialectical. Via analytic generalization in case studies, the paper proposes two models to illustrate firstly the chronological developments and secondly the socially mediated and dialectical nature of second language writing teacher cognition.